O uso de jogos no Ensino de Física: uma metodologia para o ensino de gravitação - Neves, Jordânia Chirly Alves (2020)
Nowadays, there are frequent discussions about a better model of Learning for Education in Brazil, which are a consequence of the fact that Education is considered a process that is constantly developing, where it is discussed what kind of educator and student is desired to build a country of competent and critical citizens. The present work proposes to present and report the use of a teaching sequence contributed in the use of games for learning, in a public school in the city of Araruna-PB, directed at the use of games focused on the Teaching of Gravitation, as a pedagogical strategy for the Physics Teaching. Our work aimed to have an educational product, detailing activities with a sequence of games for the Teaching of Gravitation, composed of 10 meetings, directed to stimulate the interaction between the students, enhancing a teaching approach aligned to the construction of knowledge through playfulness for a more effective learning. Subsidized by Vygotsky's Socio-Interactionist theory, we intend to lean on the idea of interaction and construction of knowledge from this theory. Thus, we aspire to offer to the high school physics teacher an intervention proposal that approaches concepts through playful activities and the use of games, allowing to the teacher's creativity to adapt and rework new games with the purpose of building new knowledge from playful activities with low-cost materials, as well as discarding the use of mathematics only as a tool to solve problems in physics and approaching it as an essential element for understanding physical concepts, thus trying to overcome the lack of meaning so commented by most students.